2014
DOI: 10.1007/s00228-014-1786-7
|View full text |Cite
|
Sign up to set email alerts
|

Drug-drug interaction software in clinical practice: a systematic review

Abstract: The deficiency of clinical relevance of detected DDIs should be addressed in the upcoming research as it would provide more relevant information to the prescribers' in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
117
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 53 publications
6
117
0
10
Order By: Relevance
“…Numerous online drugdrug interaction databases (DIDs) are available as open access or subscription resource [4][5][6][7]. Unfortunately, these often provide little consensus, if not even contradictory advice, much to the frustration of the health-care provider [4,5,[7][8][9]. Studies comparing DIDs have found substantial variations in severity classification and in the availability of underlying references and accessed knowledge resources [4][5][6][7][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous online drugdrug interaction databases (DIDs) are available as open access or subscription resource [4][5][6][7]. Unfortunately, these often provide little consensus, if not even contradictory advice, much to the frustration of the health-care provider [4,5,[7][8][9]. Studies comparing DIDs have found substantial variations in severity classification and in the availability of underlying references and accessed knowledge resources [4][5][6][7][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is impossible for health-care professionals to recognize or hold at hand knowledge on all potentially clinically relevant DDIs, and clinical support systems on drug-drug interactions have become widely available to health-care professionals worldwide. Numerous online drugdrug interaction databases (DIDs) are available as open access or subscription resource [4][5][6][7]. Unfortunately, these often provide little consensus, if not even contradictory advice, much to the frustration of the health-care provider [4,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…24 LexiInteract showed high sensitivity (87%-100%) and specificity (80%-90%) according to the studies which have evaluated the performance of the DDI screening software. [25][26][27] The 24 hour interval between administrating two drugs was used for assessing pDDI prevalence. According to the LexiInteract database pDDIs of classes A (no interaction) and B (no action needed) are of academic, but not a relevant clinical concern.…”
mentioning
confidence: 99%
“…(25) Even very simple systems can be helpful, and it generally holds true that physicians with training in geriatrics are less likely to prescribe potentially inappropriate medications. (26,27) These issues need to be given first line priority by the decision makers to allow adequate development of geriatric medicine at all levels of a health care system. The general scheme of old patient management is shown in the figure (Fig 1).…”
Section: Management After Icu Dis-chargementioning
confidence: 99%